Subject, Ideals and Intimacy: Women’s Poetic Language in the Slovenian Moderna period - Novak Popov, Irena (Slavia Centralis, 2024)
The assertion of female literary subjectivity and the representation of intimacy in the Moderna period show a loosening in traditional female roles, which had been normed by the patriarchal, predominantly rural Slovenian society. The present discussion deals with young and educated women poets who, at the beginning of their literary career in the liberal multicultural Trieste, connected around the first Slovenian women’s magazine. With idealised notions of love and personal freedom, their poetry addressed important issues of women’s existence, in both the distribution of economic and political power, and also and above all private issues: self-awareness, (failed) erotic relationships, marriage and motherhood, and the possibilities of personal fulfilment. The most ambitious ones later published their own collections. They, however, remained on the margins of cultural memory, because both literary history and the canon serve solely to confirm the self-identity of a small nation.